SOCIAL PROTECTION OF THE POPULATION – THE BASIS OF CONSTRUCTION OF A LEGAL STATE AND CIVIL SOCIETY (International Conference on Economics, Finance, Banking and Management, 2025)
The transition to a market economy has necessitated the need to introduce the concept of "social protection of the population." Social protection of the population is a system of direct targeted guarantees of the state to the population, ensuring normal conditions of life. In other words, the social protection system should be built based on solving the tasks of ensuring real socio-economic effectiveness, rather than from narrow considerations of market systems. At the same time, social protection is always objectively determined, on the one hand, by the system of economic relations, in which it operates, and on the other - by the requirements of the modern state of the world economy, of humanity as a whole.